2021
DOI: 10.1371/journal.pone.0249550
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of IgG antibodies against SARS-CoV-2 among healthcare workers in a tertiary pediatric hospital in Poland

Abstract: Data on the prevalence of the SARS-CoV-2 antibody in healthcare workers (HCWs) is scarce, especially in pediatric settings. The purpose of this study was to evaluate SARS-CoV-2 IgG-positivity among HCWs of a tertiary pediatric hospital. In addition, follow-up of the serological response in the subgroup of seropositive HCWs was analysed, to gain some insight on the persistence of IgG antibodies to SARS-CoV-2. We performed a retrospective analysis of voluntary SARS-CoV-2 IgG testing, which was made available fre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 12 publications
4
18
0
Order By: Relevance
“…Population-based serosurveys measuring anti-SARS-CoV-2 antibodies offer one method for approximating infection rates and monitoring the progress of the epidemic [ 4 ]. By identifying individuals who have established anti-viral antibodies, immunoassay, such as enzyme-linked immunosorbent assay (ELISA), can provide a more thorough understanding of the SARS-CoV-2 prevalence [ 5 ]. In fact, the current study is important to observe and trace COVID-19 incidence and recognize the frequency of or non-reported COVID-19 infections individuals in the community.…”
Section: Introductionmentioning
confidence: 99%
“…Population-based serosurveys measuring anti-SARS-CoV-2 antibodies offer one method for approximating infection rates and monitoring the progress of the epidemic [ 4 ]. By identifying individuals who have established anti-viral antibodies, immunoassay, such as enzyme-linked immunosorbent assay (ELISA), can provide a more thorough understanding of the SARS-CoV-2 prevalence [ 5 ]. In fact, the current study is important to observe and trace COVID-19 incidence and recognize the frequency of or non-reported COVID-19 infections individuals in the community.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several studies examining the prevalence of SARS-CoV-2 and the seroprevalence of IgM/IgG antibodies in HCWs compared to community levels, and results are varied [ 4 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Though there have been fewer studies of pediatric HCWs to date, rates of positive serology in pediatric HCWs have consistently been found to be lower or equal to those measured in the general population, with the reported range of positive serology ranging from 0–16.9% [ 5 , 6 , 7 , 8 , 9 , 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the potential for increased exposure to SARS-CoV-2 among healthcare workers (HCWs) has led to numerous serologic studies, the pediatric HCW population remains somewhat less well surveyed [ 4 , 5 , 6 , 7 , 8 , 9 ]. Pediatric HCW are in general exposed to a large variety of infectious diseases, and during the COVID-19 pandemic, at increased risk for both known and unknown exposure to SARS-CoV-2 given the varied presentation of COVID-19 in children.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the spatial conditions in hospital waiting rooms, it appears reasonable that the risk of viral infection is elevated due to the relatively close contact to possible SARS-CoV-2 infected patients. Furthermore, direct contact to healthcare workers may also imply an increased risk for viral transmission: Shields et al report a point prevalence of asymptomatic, SARS-CoV-2 PCR-positive healthcare works (HCW) of 2.4% and Kasztelewitz et al found, that more than 50% of the HCW, who had been tested positive for SARS-CoV-2 antibodies, denied any clinical symptoms in the past weeks prior testing, illustrating that these HCW had been asymptomatic but possibly infectious at a time [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%